Development and testing of a semi mechanical ginger peeler - ANIE JOHN S MANOJ P. K MOHAMED NIZAR U. A SATHYAN K; Er. Prince M. V (Guide) (Tavanur 1996 Department of Post-Harvest Technology and Agricultural Processing)
Abrasion unit - wooden roller
Development and testing of a semi mechanical ginger peeler